Ответы 1

  • (2a / (2a + b) - 4a^2 / (4a^2 + 4ab + b^2)) : (2a / (4a^2 - b^2) + 1 / (b - 2a)) = ((2a * (2a + b) + b - 4a^2) / (2a + b)^2) : ((2a - (2a + b)) / (2a - b) * (2a + b)) = ((4a^2 + 2ab + b - 4a^2) / (2a + b)^2)) : ((2a - 2a - b) / (2a - b) * (2a + b)) = ((2ab + b) / (2a + b)^2) : ((- b) / (2a - b) * (2a + b)) = (b * (2a + 1) * (2a - b) * (2a + b)) / ((2a + b)^2 * (- b)) = - (2a + 1) * (2a - b) / (2a + b).

    Ответ: - (2a + 1) * (2a - b) / (2a + b).

    • Автор:

      giaojxj
    • 3 года назад
    • 0
  • Добавить свой ответ

Еще вопросы

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years